Resiliensi Remaja Yatim Piatu Yang Melaksanakan Salat Tahajud - Andi Sulfahmi; Andi Ahmad Ridha (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2017)
Resilience is the capacity or the ability of an individual to be able to survive in difficult and stressful situations, and can rise from its problems. Salat tahajud is a form of practice of worship in private, which is one aspect of religiosity, where religiosity may affect resilience. This study aims to determine the relationship between the quality of prayer tahajud with resilience in adolescents orphaned at Al-fityan Foundation Branch Gowa. Subjects in this study amounted to 34 teenage orphan. The research instrument is the quality scale tahajud prayer with there liability value α = 0.840 and resilience scale with reliability value α = 0.878. The results of this study indicate that there is a positive correlation between the quality of prayer tahajud with resilience teen orphan (the correlation test was used Spearman = 0.715, p = 0.000). The higherthe quality, the higher the prayers tahajud resiliency teenage orphans at Al-Fityan Foundation Branch Gowa. Salat tahajud are carried out routinely and can improve the quality of resilience in adolescents orphaned at Al-Fityan Foundation Branch Gowa.Keywords: resilience, quality of tahajud prayer, teen orphans